Novel Screen to Assess Bactericidal Activity of Compounds Against Non-replicating Mycobacterium abscessus - Berube, Bryan J.; Castro, Lina; Russell, Dara; Ovechkina, Yulia; Parish, Tanya (Frontiers in Microbiology, 2018)
Mycobacterium abscessus infections are increasing worldwide. Current drug regimens are largely ineffective, yet the current development pipeline for M. abscessus is alarmingly sparse. Traditional discovery efforts for M. abscessus assess the capability of a new drug to inhibit bacterial growth under nutrient-rich growth conditions, but this does not predict the impact when used in the clinic. The disconnect between in vitro and in vivo activity is likely due to the genetic and physiological adaptation of the bacteria to the environmental conditions encountered during infection; these include low oxygen tension and nutrient starvation. We sought to fill a gap in the drug discovery pipeline by establishing an assay to identify novel compounds with bactericidal activity against M. abscessus under non-replicating conditions. We developed and validated a novel screen using nutrient starvation to generate a non-replicating state. We used alamarBlue® to measure metabolic activity and demonstrated this correlates with bacterial viability under these conditions. We optimized key parameters and demonstrated reproducibility. Using this assay, we determined that niclosamide was bactericidal against non-replicating bacilli, highlighting its potential to be included in M. abscessus regimens. In contrast, most other drugs currently used in the clinic for M. abscessus infections, were completely inactive, potentially explaining their poor efficacy. Thus, our assay allows for rapid identification of bactericidal compounds in a model using conditions that are more relevant in vivo. This screen can be used in a high-throughput way to identify novel agents with properties that promise an increase in efficacy, while also shortening treatment times.